PROPAGANDA PEMERINTAH ORDE BARU DALAM NOVEL LAN JANI (The Propaganda of New Order Government in the Novel Lanjani) - I Wayan Nitayadnya (SALINGKA, 2014)
To strengthen their power, the government or the ruler always give influence to the writer or the publisher to put the political material and certain ideology in the literature work. Those materials will be revealed based on the novel Lan Jani and become the aim of the article. The method which is applied in the paper is literature and analytical descriptive. The resentationin the paper will be in narrative. The analysis result is the novel has political and ideological policies of New Order Government. The disseminated propaganda of national policies is transmigration and youth village program based on Pancasila. The target aimed by New Order government is the rising of the young generation awareness about the importance of transmigration in develop the country.  In other side, the realization of youth village program based on Pancasila could raise the spirit of unity and integrity of Indonesian young  generation.